2011
DOI: 10.1177/1541204011399933
|View full text |Cite
|
Sign up to set email alerts
|

Status Offenders in the Juvenile Court

Abstract: Prior research has suggested that female status offenders are often treated more harshly than male status offenders in juvenile court processing. This finding is often explained by the traditional role perspective which suggests that the juvenile court is attempting to protect the sexuality of girls. In addition, there is theoretical and empirical evidence that the effect of gender may vary by race/ethnicity. This study examines the joint effects of gender and race/ethnicity in the adjudication of status offen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 33 publications
0
9
0
2
Order By: Relevance
“…Other types of gender non-conforming behavior that fall under the category of status offenses also receive harsher sanctions from parents, schools and courts when committed by girls as compared to boys [39][40][41], in concert with the trend toward "up-criming" of girls' misbehavior more generally [1,35,105]. Moreover, these effects may be exacerbated by race, with black and Hispanic girls receiving even harsher consequences than their white counterparts [106]. The possibility that gender-role nonconformity is a factor is suggested by research demonstrating that gender atypicality accounts for the relationship between abuse and PTSD amongst SMS youth [107].…”
Section: Sexualitymentioning
confidence: 99%
“…Other types of gender non-conforming behavior that fall under the category of status offenses also receive harsher sanctions from parents, schools and courts when committed by girls as compared to boys [39][40][41], in concert with the trend toward "up-criming" of girls' misbehavior more generally [1,35,105]. Moreover, these effects may be exacerbated by race, with black and Hispanic girls receiving even harsher consequences than their white counterparts [106]. The possibility that gender-role nonconformity is a factor is suggested by research demonstrating that gender atypicality accounts for the relationship between abuse and PTSD amongst SMS youth [107].…”
Section: Sexualitymentioning
confidence: 99%
“…The findings of this study contribute to the literature on racial and ethnic disparities in the juvenile justice system by focusing on an early stage in the decision-making process and by broadening the geographic scope of past studies (Duran & Posadas, 2013; Freiburger & Burke, 2011; Guevara, Boyd, Taylor, & Brown, 2011; Moore & Padavic, 2010). The findings highlight the way race and ethnicity influence postarrest decision making for less serious charges and point to the ongoing need to strive for equitable treatment of youth.…”
Section: Resultsmentioning
confidence: 85%
“…Black girls compared with White girls are more likely to be recommended for formal processing (Bishop et al, 2010) and receive harsher dispositions, including commitment to correctional facility and transfer to adult court (Moore & Padavic, 2010). Hispanic girls also experience more severe dispositions such that they are more likely to be found delinquent than White girls even after accounting for important individual and case characteristics (Freiburger & Burke, 2011). These findings are consistent with the notion that intersecting subordinate identities may create a cumulative disadvantage for members of racial and ethnic minority groups (Samuels & Ross-Sheriff, 2008).…”
Section: The Effects Of Legal Extralegal and Contextual Factors On Dmcmentioning
confidence: 99%
“…Studies have found that females enjoy leniency compared to males, especially for delinquent offenses (Bishop & Frazier, 1992, 1996Evangelist et al, 2017;Johnson & Scheuble, 1991;Maggard et al, 2013) while others have found that females are treated more harshly than males, particularly for status and "bootstrapping" offenses 1 (Bishop & Frazier, 1996;Chesney-Lind, 1977). These relationships are sometimes complicated by race, with some studies finding that girls from racial and ethnic minority groups do not benefit from the leniency afforded to white girls (Freiburger & Burke, 2011).…”
Section: Gendermentioning
confidence: 99%